The tidal swamp lands in Indonesia are potential areas for increasing food production especially rice. About 250.000 hectares of the swampy areas in suamtra and Kalimantan have been developed for rice production. Tidal swamp land has many interconnecting natural habitats wgich are economically and scientifically important. Agronomic activities in rice fields might have detrimental effects on other habitats. Therefore, agrochemicals especially pesticides for pest control, have to be carefully app - Uha Saharja Satari; Soemartono Sosromarsono (Buletin Hama dan Penyakit Tumbuhan, 1979)
The tidal swamp lands in Indonesia are potential areas for increasing food production especially rice. About 250.000 hectares of the swampy areas in suamtra and Kalimantan have been developed for rice production. Tidal swamp land has many interconnecting natural habitats wgich are economically and scientifically important. Agronomic activities in rice fields might have detrimental effects on other habitats. Therefore, agrochemicals especially pesticides for pest control, have to be carefully applied based on sound ecological approach. A Kind of pest management model is presented which consits of compatible combination of cultural control, use of resistant varieties, sanitation, and chemical control with environmentally least toxic pesticides if it is needed base on pest population count.